1985
DOI: 10.1002/cne.902350306
|View full text |Cite
|
Sign up to set email alerts
|

Corticopontine projection in the macaque: The distribution of labelled cortical cells after large injections of horseradish peroxidase in the pontine nuclei

Abstract: We studied the distribution of corticopontine cells in the monkey cerebral cortex. Horseradish peroxidase (HRP) was injected into the brainstem of monkeys in an attempt to fill the pontine nuclei on one or both sides. In control animals we injected the medullary pyramids or varied the route, size, or location of pontine injections. All retrograde filled corticopontine neurons were layer V pyramidal cells. Corticopontine cells were distributed within a largely continuous area of cortex which extended from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
231
1
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(252 citation statements)
references
References 36 publications
19
231
1
1
Order By: Relevance
“…We found second-order neurons labeled with RV in cortical areas and in regions of the parvocellular portion of the red nucleus (Fig. 3A) that are known to project to the first-order neurons in the pontine nuclei and the inferior olive (9,13).Surprisingly, we also found substantial numbers of secondorder neurons labeled with RV in the STN predominantly on the side contralateral to the injection site (Figs. 1, 2B, 3, and 4).…”
mentioning
confidence: 66%
“…We found second-order neurons labeled with RV in cortical areas and in regions of the parvocellular portion of the red nucleus (Fig. 3A) that are known to project to the first-order neurons in the pontine nuclei and the inferior olive (9,13).Surprisingly, we also found substantial numbers of secondorder neurons labeled with RV in the STN predominantly on the side contralateral to the injection site (Figs. 1, 2B, 3, and 4).…”
mentioning
confidence: 66%
“…It is well known that cortical afferents to the cerebellum arise from multiple areas of the cerebral cortex including frontal, parietal and temporal lobes (Schmahmann & Pandy, 1997;Glickstein et al 1985). However, the thalamic relays of cerebellar efferents reaching the cortex are not clearly defined in various species.…”
Section: Discussionmentioning
confidence: 99%
“…The cortico pontine projection is an extremely large pathway, thought to contain more fibers than the pyramid and to comprise the majority of the fibers in the cerebral peduncle (Tomasch, 1969). In monkeys, some investigators have found the greatest density of corticopontine neurons in precentral cortex (area 4) (Brodal, 1978;Wiesendanger et aI., 1979), while others have found the density in premotor cortex (area 6) and frontal eye fields (area 8) to be as great or greater (Glickstein et al, 1981;Leichnetz et aI., 1984). Prefrontal cortex (areas 9 and 10) and post central cortex (areas 3, 1, and 2) also give rise to a substantial number of corticopontine fibers, while the remainder of the parietal lobe (areas 5 and 7), some regions of the temporal lobe (areas 21 and 22), and the lateral visual cortex (areas 18 and 19) give rise to smaller numbers of fibers.…”
Section: Discussionmentioning
confidence: 99%